Penyelesaian Sengketa Perjanjian Syariah pada Lembaga Keuangan Syariah - Maskufa, Maskufa (Faculty of Shariah and Law, 2013)
Dispute settlement in Islamic tradition has been carried out since the era of Prophet Muhammad SAW. This is done through the courts (litigation) and through shulh, fatwa, mazhalim, and hisbah, known as non-litigation. The form of muamalah dispute settlement especially applicable nowadays is almost the same as those prevailing at the time of the Prophet. Litigation through the judicial institutions and non-litigation settlement called as alternative dispute resolution (ADR) is known by the term shulh in fiqh, while the path through arbitration is knows in fiqh as tahkimDOI: 10.15408/aiq.v5i1.2113